The early drawings of Malaya ( 1880-1894) by Frank Swettenham - Abdullah, Sarena (Pusat Pengajian Seni, Universiti Sains Malaysia, 2009)
This paper discusses the drawings and watercolours produced by Frank Swettenham during his career period in Malaya. Frank Swettenham or Sir FrankAthelstaneSwettenham (1850.1946) was the Former Resident. the first Resident General of the Federated Malay States (F.M.S), then the Governor of the Straits Settlement and the High Commissioner of the F.M.S. His skill, tact, tolerant cynicism and self confidence, supported by his fluency in the Malay language and his vast knowledge of the Malay custom had helped him in developing and building relationship with the Malay Sultans, which eventually led to the formation of the F.M.S. and changed the British policy towards the Malay States after 1860s.